UJI VALIDITAS KONSTRUK TES KEPRIBADIAN BIG FIVE DENGAN TWO-ALTERNATIVE FORCED CHOICE PADA KARYAWAN BUMN - Atsal Nurprayoga; Moh. Abdul Hakim (Jurnal Ilmu Perilaku, 2025)
Personality assessments help companies maintain the quality of human resources (HR) and develop potential efficiently. The use of personality assessment in Indonesia faces challenges, such as limited tools relevant to the times and the practice of buying and selling test kits. To face these challenges, state-owned company PT X developed a Big Five personality test using the two-alternative forced choice (2AFC) method. This study aims to test the construct validity of the Big Five personality test developed by BUMN PT X with a sample of BUMN employees. The data analysis technique used confirmatory factor analysis (CFA). The research subjects consisted of 3,989 employees at the Officer Position Level. The results showed that the Big Five personality test developed by BUMN PT X has good construct validity, with all dimensions having a fit model. It is shown from the overall model fit assessment (Chi-square, SRMR, RMSEA, CFI, and TLI) that it meets the expected value index. The results also show residual covariance in four dimensions (openness to experience, conscientiousness, agreeableness, and neuroticism). The findings show that the personality test tool developed shows adequate construct validity in measuring employees' Big Five personalities. This personality test will help companies make decisions when managing human resources, especially in the BUMN environment.